IDENTIFYING THE CAUSES OF TEAM EFFECTIVENESS PROBLEM IN A NEW VENTURE TEAM. STUDY: AGRI-CULTURED - Dewanto Azhari, Pratama
Entrepreneurship activities around the world are growing. Entrepreneurs carry out their entrepreneurial activities by creating a new venture called startup. This new venture called startup is by no means an individual sport. Therefore, a new venture team's effectiveness is an important aspect in the entrepreneurial process of creating a successful startup. In this study, the author wants to explore the causes of team effectiveness problems in the startup called 'Agri-Cultured'. Agri-Cultured is a startup founded by four students from the Entrepreneurship Program in SBM ITB. The CEO of Agri-Cultured states that the idea of the project itself has a lot of potential, but the team is not good enough to be able to maximize the potential that the project has. The project will use the Team Effectiveness Questionnaire (TEQ) that divides team effectiveness to eight interconnected dimensions. In doing the research, the author starts by conducting a preliminary questionnaire using the TEQ, the result from the questionnaire will be the basis of the in-depth interview data collecting process. The data collected from the interview will be analyzed using a qualitative descriptive method. From the preliminary questionnaire it is found that there are two problematic dimensions. However, when explored further from the in-depth interview, there are problems identified in seven out of eight dimensions in Agi-Cultured. From those problems, there are three core factors identified as the causes of the problems. It is found that Agri-Cultured sole purpose to fulfill academic requirements, inability to develop relationships through online communications, and the unfitness of the curriculum in accommodating the students' business is identified as the core factors that cause team effectiveness problem in Agri-Cultured. Based on the findings of this research the author gives recommendations to Agri-Cultured, entrepreneurs, Entrepreneurship Program in SBM ITB and future researchers who are interested in tackling this topic. Keywords: Team Effectiveness, New Venture Team, Team Effectiveness Problem